2016
DOI: 10.1007/s11695-016-2164-6
|View full text |Cite
|
Sign up to set email alerts
|

An Exploration of System-Level Factors and the Geographic Variation in Bariatric Surgery Utilization

Abstract: There is wide geographic variation in bariatric surgery rates, although higher regional rates of obesity are not correlated with higher rates of surgery. In this study, four system-level factors were explored as contributors to this geographic variation. Geographic utilization rates of bariatric surgery showed no correlation to the number of bariatric surgeons, number of accredited centers, and the percentage of patients with a recent primary care visit. The total number of surgical discharges was weakly corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Such an analysis would complement a prior non-VA study that examined contributors to geographic variation in bariatric surgery in Medicare, which found no association between undergoing bariatric surgery and system-level factors, such as the number of bariatric surgeons, number of surgical centers, or percentage of patients with recent primary care utilization. 29 Only through such investigation can modifiable factors at each level be clearly identified and then modified using evidence-based change strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Such an analysis would complement a prior non-VA study that examined contributors to geographic variation in bariatric surgery in Medicare, which found no association between undergoing bariatric surgery and system-level factors, such as the number of bariatric surgeons, number of surgical centers, or percentage of patients with recent primary care utilization. 29 Only through such investigation can modifiable factors at each level be clearly identified and then modified using evidence-based change strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, other authors found that having centres of excellence did not result in impaired access to care. Another study reported a trend towards a positive correlation between the number of bariatric centres in a hospital referral region and bariatric surgery rates. Although the association was not as strong as in the present study, it is possible that there is a saturation point above which increasing the number of centres would not increase care delivery, and that many hospital referral regions in the USA may have reached such a threshold.…”
Section: Discussionmentioning
confidence: 96%
“…In a survey of 478 physicians in the United States, the most commonly reported reason for not referring for bariatric surgery was being “unacquainted with local bariatric surgeon” [23]. Another study investigating system-level factors within U. S. hospital referral regions found no association between bariatric surgery provision and the number of bariatric surgeons, number of accredited centers, or percent of patients with a recent PCP visit [38].…”
Section: Contextual Factorsmentioning
confidence: 99%